Intra-Substance Steroid Injection for Full-Thickness Supraspinatus Tendon Rupture - Haleem, Waqas; Khan, Absar; Hamid, Abdul; Hussain, Tajammul; Waqar, M.; Arif, M. (Biological and Clinical Sciences Research Journal, 2025)
Full-thickness rotator cuff tears, particularly of the supraspinatus tendon, cause significant pain and disability. Although corticosteroid injections are widely used for shoulder pathologies, their role in managing complete tendon ruptures remains controversial. Objective: To evaluate the efficacy and safety of local corticosteroid injection in improving pain and functional outcomes among patients with full-thickness supraspinatus tears. Methods: This prospective interventional study was conducted in the Orthopedic Unit of Hayatabad Medical Complex, Peshawar, from February 20 to September 21, 2024. A total of 18 patients with full-thickness supraspinatus tears, as determined by clinical assessment and MRI findings, were enrolled after obtaining informed consent. Each patient received an ultrasound-guided injection of 1 ml of 2% xylocaine mixed with 1 ml of Depo-Medrol® (methylprednisolone acetate 40 mg/ml) at the tear site. Pain and functional outcomes were assessed using the Visual Analogue Scale (VAS) and the Shoulder Pain and Disability Index (SPADI) before the injection, 2 weeks after, and 3 months after. Data were analyzed using descriptive statistics and comparative analysis of pre- and post-injection scores. Results: The mean baseline SPADI pain score was 63 (range: 52–72), SPADI disability score 49.66 (34–65), SPADI total score 47.4 (31–62), and VAS score 6.5 (5–8). At three months post-injection, significant improvement was observed, with the SPADI pain score reduced to 34.5 (20–49), the disability score to 30.5 (18–43), the total score to 32.5 (19–47), and the VAS score to 4 (3–6). No serious adverse effects were reported. Conclusion: A combined injection of corticosteroid and local anesthetic directly into the ruptured supraspinatus tendon significantly reduces pain and enhances shoulder function in patients with full-thickness rotator cuff tears, offering a safe and minimally invasive therapeutic option.